ANALISIS YURIDIS TERHADAP KEKUATAN PEMBUKTIAN AKTA PPAT DALAM PERKARA NO 152/PDT.G/2017/PN PTK - Zakaria, Zakaria; Wiko, Garuda; Rachmawati, Rachmawati (Tanjungpura Acta Borneo Jurnal, 2023)
AbstractThe land dispute in decision Number 152/Pdt.G/2017/PN.PTK is an interesting case because the lawsuit is based on the non-recognition of the signing of the deed of sale and purchase which is not based on the participant who signed but get sued by the plaintiffs which are grandchildren of participant in the deed of sale and purchase, and Plaintiff III is the great-grandson of the reported participant based on the criminal report of theft. This study has the following research objectives, to analyze the strength of the proof of the sale and purchase deed which was determined based on the decision no. 152/Pdt.G/2017/PN Ptk. by using a normative juridical research methodology, the results obtained in the form of proof of the deed carried out are the fulfillment of formal aspects as carried out by Land Titles Registrar, it can be noted that if what the defendant did was a conscious act of law, that land ownership must be carried out based on normative aspects, and proof of the legality of land ownership, so that the strength of the proof of the deed that occurred in the civil case no. 152/PDT.G/2017/PN PTK is a form of verification that is prioritized because it uses a formal approach in the issuance of a deed of sale and purchase. And it can be concluded also if the determination of the plaintiffs in the lawsuit is an error in persona lawsuit because the parties have not been determined to be heirs by the Religious Courts, so they do not have Legal Standing as heirs who have rights to inheritance.  AbstrakKasus sengketa tanah pada putusan perkara Nomor 152/Pdt.G/2017/PN.PTK merupakan kasus yang menarik sebab gugatan didasari oleh ketidak pengakuan atas penandatangan akta jual beli yang bukan didasari oleh pihak yang bertanda tangan namun digugat oleh para penggugat yang merupakan cucu dari pihak dalam akta jual beli, dan penggugat III merupakan cicit dari pihak yang dilaporkan berdasarkan laporan pidana penyerobotan. Penelitian ini memiliki tujuan penelitan sebagai berikut, yaitu untuk menganalisis kekuatan pembuktian akta jual beli yang ditetapkan berdasarkan putusan No. 152/Pdt.G/2017/PN Ptk. dengan menggunakan metodologi penelitian yuridis normatif, maka didapatkan hasil penelitian berupa pembuktian akta yang dilakukan merupakan pemenuhan aspek-aspek formil sebagaimana yang dijalankan oleh PPAT, dapat diperhatikan jika yang tergugat lakukan merupakan tindakan sadar hukum, bahwa kepemilikan tanah haruslah dilakukan berdasarkan aspek-aspek normatif, dan bukti legalitas dari kepemilikan tanah, sehingga kekuatan pembuktian akta yang terjadi pada perkara perdata No. 152/PDT.G/2017/PN PTK merupakan salah satu bentuk dari pembuktian yang diprioritaskan sebab menggunakan pendekatan formil dalam penerbitan akta jual beli. Dan dapat disimpulkan juga jika penetapan dari para pihak penggugat dalam gugatan merupakan gugatan error in persona sebab para pihak belum ditetapkan menjadi ahli waris oleh Pengadilan Agama, sehingga tidak memiliki Legal Standing sebagai ahli waris yang memiliki hak atas harta waris.